Versican and the Regulation of Cell Phenotype in Disease - Wight, Thomas N. (2014)
BACKGROUND: Versican is an extracellular matrix (ECM) proteoglycan that is present in the pericellular environment of most tissues and increases in many different diseases. Versican interacts with cells to influence the ability of cells to proliferate, migrate, adhere and assemble an ECM. SCOPE OF REVIEW: The structure of the versican molecule is briefly reviewed and studies highlighting those factors that promote versican synthesis and degradation and their impact on cell phenotype in disease are discussed. Particular attention is given to vascular disease, but other diseases where versican is important are covered as well, most notably different forms of cancers. Attention is given to mechanisms(s) by which versican influences cell behaviors through either direct or indirect processes. Versican produced by either stromal cells or myeloid cells can have a major impact influencing immunity and inflammation. Finally, studies controlling versican accumulation that either delay or inhibit the progression of disease will be highlighted. MAJOR CONCLUSIONS: Versican is one component of the ECM that can influence the ability of cells to proliferate, migrate, adhere, and remodel the ECM. Targeting versican as a way to control cell phenotype offers a novel approach in the treatment of disease. SIGNIFICANCE: ECM molecules such as versican contribute to the structural integrity of tissues and interact with cells through direct and indirect means to regulate, in part, cellular events that form the basis of disease.